Evaluation of Culture Media, pH and Temperature for Optimal Growth of Leucopaxillus giganteus: An Indian Wild Mushroom - Feleke, Hirut Tsegaye; Doshi, Anila (Mushroom Research, 2017)
The present study reports the influence of growth factors such as culture media, incubation temperature and initial pH of the media on mycelial growth of Leucopaxillus giganteus. Five different culture media (MMN, SMY, PDA, 1 and 2% MEA) under various growth temperatures (20, 25, 30, 35 ±1 °C) and pH values (5, 5.5, 6, 6.5, 7 and 7.5) were checked in order to achieve the best condition for mycelium growth of Leucopaxillus giganteus. Huge variations were observed in the growth performance of the species against the different growth factors. The maximum mycelial growth was obtained at the end of 30 days when the species cultured on MMN media at 25 °C with initial pH 6.  Fast mycelia growth was observed on SMY media at 30 °C. A better growth performance was observed on slightly acidic media and the dry weight of the mycelia was varied with both; type and pH of the media. The mycelia of Leucopaxillus giganteus were cottony and white gray, forming sectored on PDA media, while, the mycelium was fluffy and white on MMN and SMY culture media. The present investigation clearly showed that the mycelial growth of Leucopaxillus giganteus was highly dependent on the growth factors.